Spatial Structure and Decadal Spatiotemporal Distribution of the Anchoveta ( Engraulis ringens ) in the Marine Ecosystem of the Peruvian Current Between 1985 and 2024 - Pedro Ramiro Castillo; Han Xu; Gustavo Cuadros; Daniel Grados; Carlos Valdez; Rodolfo Cornejo; Marissela Pozada‐Herrera (Fisheries Oceanography, 2025)
This paper presents the spatial structure with geostatistical analysis and decadal spatiotemporal distribution of anchoveta according to the Pacific Decadal Oscillation index, its implications for the anomalous events of the oceanographic conditions of the Northern Region of the Humboldt Current System (NRHCS), and areas of high anchoveta abundance found in the analyzed period. The acoustic data came from the Hydroacoustic Pelagic Resources Assessment Surveys carried on by the Instituto del Mar del Peru (IMARPE), and the oceanographic data came from satellite images of sea surface thermal anomalies (SSTA) between 1985 and 2024. The results showed that anchoveta has had a positive linear trend, with a high positive spatial autocorrelation and a structure spatially dependent on invironmental conditions in space and time. In the cold decadal periods, anchoveta were found a little far from the coast, distributed in high concentrations mainly in the north‐central region, while in the warm decadal periods, they were found close to the coast and with greater abundance towards the central zone; exceptional was in the warm period of 1985–1988, where anchoveta distribution was wide and generally dispersed. The trend in the warm decadal periods was negative, and in the decadal periods, it was positively influenced by El Niño events: 1997–1998 and 2015–2016, with a decrease in biomass recorded in 1998 and 2015. In the last cold period, 2017–2024, it was influenced by the warm year of 2023. Between 2000 and 2024, anchoveta biomass averaged 8.26 million tons, with an average biomass of 7.46 million tons for the north‐central region between 2004 and 2024.

Distribution and abundance of squat lobster (Pleuroncodes monodon) and its association with anchoveta in the coastal zone of the Peruvian Current (1998–2024) - Pedro Ramiro Castillo; Luis La Cruz; Carlos Valdez; Gustavo Cuadros; Ketty Ferrel; Marissela Pozada-Herrera; Rodolfo Cornejo; Aníbal Aliaga; Daniel Grados (Frontiers in Marine Science, 2025)
The squat lobster or munida ( Pleuroncodes monodon ) is one of the most abundant species in the coastal zone of the Peruvian Current. Due to its high incidence of occurrence and biomass, it has been monitored since 1998 by the Instituto del Mar del Perú (IMARPE) through the Hydroacoustic Assessment Surveys for Anchoveta and Other Pelagic Resources. In this study, 59 surveys conducted between 1998 and 2024 were analyzed to study the spatial distribution, abundance, and ecological relationship of munida with anchoveta ( Engraulis ringens ). The results showed that between 1998 and 2000, munida expanded its distribution northward along the Peruvian coast, while from 2001 onward its range remained relatively stable. A clear seasonal pattern was identified: during winter and spring, both the distribution area and inertia increased, and the species tended to occur farther from the coast, whereas in summer and autumn the distribution contracted, except during anomalous oceanographic events (e.g., warm or cold conditions). Vertically, munida generally inhabited the surface layer down to approximately 168 m, although during the 2015 -2016 El Niño event it was recorded as deep as 203 m. The average biomass throughout the study period was close to 2.04 million tons, with a maximum of 5.38 million tons recorded during survey 1703-04. Munida was also the species most closely associated with anchoveta, and when both occurred together, their interaction varied depending on the time of day, probably reflecting diel vertical migration and differential aggregation behaviors. These findings suggest that munida is a key component of the Peruvian Current ecosystem, whose variability is influenced both by seasonal cycles and by anomalous oceanographic conditions, and that its association with anchoveta may have implications for ecosystem functioning and fisheries management in the region.

Detection of harmful algal blooms from satellite-based inherent optical properties of the ocean in Paracas Bay – Peru - Carlos Paulino; Sonia Sánchez; Edward Alburqueque; Alberto Lorenzo; Daniel Grados (Marine Pollution Bulletin, 2024)

The oxygen minimum zone relative depth is a key driver of dolphin habitats in the northern Humboldt Current System - Miguel A. Llapapasca; Mario A. Pardo; Daniel Grados; Javier Quiñones (Frontiers in Marine Science, 2022)
Highly mobile odontocetes need habitats with environmental conditions with the potential of aggregating enough and high-quality prey, to maximize foraging success. Until now, the characterization of those habitats was in terms of physical and biological indicators of high production, capable of attracting and sustaining prey. Nevertheless, there has been no approach to quantifying the effects of a biophysical characteristic of the ocean with proven effects on the vertical distribution of prey for cetaceans: The oxygen minimum zone (OMZ) depth. In the northern branch of the Humboldt Current System off Peru (~6-18° S), a shallow OMZ (30-50 m) affects the distribution of the Peruvian anchovy ( Engraulis ringens ), main prey for several marine predators, including dolphins. We hypothesized these predators would aggregate in productive areas, but with preference for places where the relative OMZ depth can constrain prey vertically, making it more accessible and maximizing foraging success. We fitted Bayesian habitat models for three dominant odontocete species in this region, with multiple combinations of environmental covariates, smoothing techniques, and temporal and spatial random effects. Cetacean data came from 23 dedicated surveys spanning 2001-2019. Habitat predictors included the spatial anomalies of sea surface temperature, surface chlorophyl- a , pycnocline depth and OMZ depth. Dusky ( Lagenorhynchus obscurus ) and common dolphins ( Delphinus delphis ) preferred productive, cold areas with a very shallow OMZ, regardless of the season, while bottlenose dolphins ( Tursiops truncatus ) aggregated in both cold and warm waters, also with shallow OMZ. The former two species of higher metabolic demands would maximize energy intake by selecting areas with highly aggregated prey, while the latter, of more moderate metabolic needs and more diverse prey, would exploit less restricted habitats.

Characteristics of anchoveta ( Engraulis ringens ) schools in the optimum zone and the physiological stress zone of its distribution between 2011 and 2021 - Pedro Ramiro Castillo; Cecilia Peña; Daniel Grados; Luis La Cruz; Carlos Valdez; Marissela Pozada‐Herrera; Rodolfo Cornejo (Fisheries Oceanography, 2022)
This study has considered anchoveta acoustic data from the Pelagic Resources Hydroacoustic Assessment Surveys carried out by the Peruvian Sea Institute (IMARPE) and free access satellite data (HYCOM and MODIS from the USA) of some oceanographic variables between the period 2011 and 2021, to know the oceanographic conditions, characteristics of schools and size structure in the optimum zone (OZ) and in the physiological stress zone (PSZ), of their total distribution. The OZ is determined by the extent of the Cold Coastal Waters (CCW), and the PSZ is determined by the mixing of waters, to the north by the CCW‐ESW (Equatorial Surface Waters) and to the west between the CCW‐SSW (Subtropical Surface Waters). The range of sea surface temperature and salinity in the PSZ (16.1–25.0°C and 34.65–35.29, respectively) was wider than in the OZ (14.5–24.0°C and 34.65–35.20, respectively), where a higher number of schools were recorded. Our analyses showed that the morphometric and energetic acoustic descriptors of anchoveta schools in the summer were higher during summers compared to springs. In terms of positional characteristics, the mean depth of the schools in the PSZ was slightly greater than in the OZ. The total size structure of anchoveta in the OZ consisted mainly of juvenile specimens (less than 12 cm total length) in the summer of 2011 and 2013–2014 and in the spring between 2014–2017 and 2021. In the PSZ, adult specimens (greater than 12 cm total length) predominated in summer between 2011–2013, 2015, 2018, and 2021 and in spring between 2011–2013, 2015, and between 2018–2021. However, specimens greater than 10 cm in total length were found in the PSZ. Knowledge of the location of this zone away from the coast will allow a high probability of anchoveta capture of adult specimens during fishing periods.

Landowner Willingness to Accept Monetary Compensation for Managing Forests for Ecosystem Services in the Southern United States - Ram K Adhikari; Robert K Grala; Daniel R Petrolia; Stephen C Grado; Donald L Grebner; Anusha Shrestha (Forest Science, 2022)
Distributional specifications of the willingness-to-accept function affect the accuracy of welfare estimates when the contingent valuation model includes unsure responses. By exponentiating the bid variable, we implemented an improved methodological approach to estimate four discrete choice models reflecting treatment of unsure responses. Landowners required an average compensation of $93 acre−1 year−1 to participate in a 10-year conservation program. The probability of participation was positively influenced by payment amount, concern about wildlife habitat loss, contact frequency with the Natural Resources Conservation Service, and education level. Findings will help determine regional-level budgets for various conservation scenarios facilitating an increased production of ecosystem services. Study Implications Conservation agencies can decrease landowner uncertainty that arises from limited information about conservation programs and motivate landowners to enroll in a conservation program facilitating an increased production of ecosystem services by offering adequate monetary incentives. Conservation agencies can provide similar financial compensation for conservation of bottomland hardwoods and pine stands but will most likely need to offer greater compensation for the protection of forests prone from impacts by wildfires, hurricanes, and tornadoes. Available funding should be prioritized for conservation of critical habitats and freshwater sources vulnerable to land disturbances.

Rapid Assessments of Leatherback Small-Scale Fishery Bycatch in Internesting Areas in the Eastern Pacific Ocean - Clara Ortiz-Alvarez; Mariela Pajuelo; Daniel Grados; Marino E. Abrego; Ana Rebeca Barragán-Rocha; Mariano Barrantes; Alejandro Cotto Sánchez; Luis G. Fonseca; Velkiss Gadea Espinal; Jeffrey C. Mangel; Juan M. Rguez-Baron; Pilar Santidrian-Tomillo; et al. (Frontiers in Marine Science, 2020)

Multifarious anchovy and sardine regimes in the Humboldt Current System during the last 150 years - Renato Salvatteci; David Field; Dimitri Gutiérrez; Tim Baumgartner; Vicente Ferreira; Luc Ortlieb; Abdel Sifeddine; Daniel Grados; Arnaud Bertrand (Global Change Biology, 2018)
The Humboldt Current System ( HCS ) has the highest production of forage fish in the world, although it is highly variable and the future of the primary component, anchovy, is uncertain in the context of global warming. Paradigms based on late 20th century observations suggest that large‐scale forcing controls decadal‐scale fluctuations of anchovy and sardine across different boundary currents of the Pacific. We develop records of anchovy and sardine fluctuations since 1860 AD using fish scales from multiple sites containing laminated sediments and compare them with Pacific basin‐scale and regional indices of ocean climate variability. Our records reveal two main anchovy and sardine phases with a timescale that is not consistent with previously proposed periodicities. Rather, the regime shifts in the HCS are related to 3D habitat changes driven by changes in upwelling intensity from both regional and large‐scale forcing. Moreover, we show that a long‐term increase in coastal upwelling translates via a bottom‐up mechanism to top predators suggesting that the warming climate, at least up to the start of the 21st century, was favorable for fishery productivity in the HCS .

Biological characteristics of the hydrological landscapes in the B ay of B iscay in spring 2009 - Ainhoa Lezama‐Ochoa; Daniel Grados; Anne Lebourges‐Dhaussy; Xabier Irigoien; Alexis Chaigneau; Arnaud Bertrand (Fisheries Oceanography, 2015)
In the present study we investigated the biogeography of macrozooplankton and fish biomass in the B ay of B iscay. In this region, we defined six different landscapes based on the hydrogeographical characteristics observed in spring 2009. We then related landscape's characteristics and environmental parameters such as light attenuation depth and chlorophyll‐ a with macrozooplankton and fish acoustic biomass. Hydrodynamic structures together with coastal influences (river discharges, predation pressure and depth preference) and vertical thermohaline structure/mixing (feeding modes and ability to stay in preferred layers) appeared as the main factors determining the biological distribution. Besides, variance partitioning was used to assess the respective roles played by the hydrological environment, the geographical space and the biological environment alone, and their interactions. Results revealed that: (i) macrozooplankton and fish have a preference for different hydrogeographical landscapes; (ii) the association between hydrological conditions and geographical features, i.e. the spatial structure of the hydrological environment, plays a key role in the distribution of macrozooplankton; and (iii) prey–predator relationships have to be taken into account to provide a comprehensive characterization of habitat suitability.

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.